An exploratory study on the information avoidance behavior of the Bachelor of Library and Information Science students of the University of the Philippines Diliman in the context of academic goal progress - Baxa, Patricia Marie L.
Much of the literature on the information behavior explore information seeking. Active acquisition of information is attributed to knowledge and certainly, whereas avoidance has always been perceived as counter to the norm of information seeking. However, there are various motivations for which avoidance could actually be considered as a rational behavior. It is in this regard that this research explored avoidance behavior in the relevant context of academic goals progress.